Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Removal of toxic metals from solution by leaf, stem and root phytomass of Quercus ilex L. (holly oak). - Prasad, M N; Freitas, H (Environmental pollution (Barking, Essex : 1987), 2000)
Increased consciousness for safeguarding the aqueous environment has prompted a search for alternative technologies for the removal of toxic metal ions from aqueous solutions. In this regard, a wide variety of biomass is being considered as adsorbents of heavy metals for treatment of industrial and domestic wastewaters as well as natural waters, including drinking water. In the present investigation, the potential of Quercus ilex phytomass from stem, leaf and root as an adsorbent of chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd) and lead (Pb) at ambient temperature was investigated. The metal uptake capacity of the root for different metals was found to be in the order: Ni>Cd>Pb>Cu>Cr; stem Ni>Pb>Cu>Cd>Cr; and leaf Ni>Cd>Cu>Pb>Cr. The highest amount adsorbed was Ni (root>leaf>stem). Data from this laboratory demonstrated that Ni is sequestered mostly in the roots, where concentrations can be as high as 428.4 ng/g dry wt., when 1-year-old seedlings were treated with Ni (2000 mg/l) in pot culture experiments, compared to 7.63 ng/g dry wt., control (garden and greenhouse soil) topsoil where Ni was present in trace amounts. This proves that the root biomass of Q. ilex has the capacity for complexing Ni. Cr exhibited the least adsorption values for all the three types of phytomass compared to other metals. The trend of adsorption of the phytomass was similar for Ni and Cd, i.e. root>leaf>stem. Desorption with 10 mM Na(4) EDTA was effective (55-90%) and, hence, there exists the possibility of recycling the phytomass. The biosorption results of recycled phytomass suggest that the selected adsorbents are re-usable. The advantages and potential of the Q. ilex phytomass as a biofilter of toxic trace metals, the scope and need for enhancing the efficiency of the Q. ilex phytomass as an adsorbent of metals are presented.
Keywords: Biosorption; cadmium; chromium; copper; desorption; lead; Nickel; phytomass; Quercus ilex; root; stem

Removal of toxic metals from solution by leaf, stem and root phytomass of Quercus ilex L. (holly oak). - Prasad, M. N.; Freitas, H. (Environmental pollution (Barking, Essex : 1987), 2000)
Increased consciousness for safeguarding the aqueous environment has prompted a search for alternative technologies for the removal of toxic metal ions from aqueous solutions. In this regard, a wide variety of biomass is being considered as adsorbents of heavy metals for treatment of industrial and domestic wastewaters as well as natural waters, including drinking water. In the present investigation, the potential of Quercus ilex phytomass from stem, leaf and root as an adsorbent of chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd) and lead (Pb) at ambient temperature was investigated. The metal uptake capacity of the root for different metals was found to be in the order: Ni>Cd>Pb>Cu>Cr; stem Ni>Pb>Cu>Cd>Cr; and leaf Ni>Cd>Cu>Pb>Cr. The highest amount adsorbed was Ni (root>leaf>stem). Data from this laboratory demonstrated that Ni is sequestered mostly in the roots, where concentrations can be as high as 428.4 ng/g dry wt., when 1-year-old seedlings were treated with Ni (2000 mg/l) in pot culture experiments, compared to 7.63 ng/g dry wt., control (garden and greenhouse soil) topsoil where Ni was present in trace amounts. This proves that the root biomass of Q. ilex has the capacity for complexing Ni. Cr exhibited the least adsorption values for all the three types of phytomass compared to other metals. The trend of adsorption of the phytomass was similar for Ni and Cd, i.e. root>leaf>stem. Desorption with 10 mM Na(4) EDTA was effective (55-90%) and, hence, there exists the possibility of recycling the phytomass. The biosorption results of recycled phytomass suggest that the selected adsorbents are re-usable. The advantages and potential of the Q. ilex phytomass as a biofilter of toxic trace metals, the scope and need for enhancing the efficiency of the Q. ilex phytomass as an adsorbent of metals are presented.
The following values have no corresponding Zotero field: accession-num: 15092842
Keywords: Biosorption; cadmium; chromium; copper; desorption; lead; Nickel; phytomass; Quercus ilex; root; stem